2018
DOI: 10.1074/jbc.m117.818526
|View full text |Cite
|
Sign up to set email alerts
|

Stop codon readthrough generates a C-terminally extended variant of the human vitamin D receptor with reduced calcitriol response

Abstract: Although stop codon readthrough is used extensively by viruses to expand their gene expression, verified instances of mammalian readthrough have only recently been uncovered by systems biology and comparative genomics approaches. Previously, our analysis of conserved protein coding signatures that extend beyond annotated stop codons predicted stop codon readthrough of several mammalian genes, all of which have been validated experimentally. Four mRNAs display highly efficient stop codon readthrough, and these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 80 publications
(107 reference statements)
2
55
0
4
Order By: Relevance
“…However, we have classified a tRNA-Sup-CTA in Pan troglodytes (chimpanzee) as active, although experimentation is necessary to support that this tRNA is actively transcribed. While nonsense suppression via readthrough by near-cognate tRNAs has been demonstrated several times in metazoa (Jungreis et al 2011;Yacoubi et al 2012;Loughran et al 2018;Roy et al 2015) and suppressor tRNAs have been found in other species (Beier and Grimm 2001;Valle, Morch, and Haenni 1987), evidence for an actively transcribed suppressor tRNA in a primate species is of great interest for future experimentation. This tRNA gene is a wellconserved ortholog of the human tRNA-Gln-CTG-6-1 gene, and exhibits several chimpanzee-specific nucleotide substitutions ( Supplementary Figure 4) that are not expected to significantly impair the function of its transcript.…”
Section: Figure 2: Classification Of Expression Based On Genomic Datamentioning
confidence: 99%
“…However, we have classified a tRNA-Sup-CTA in Pan troglodytes (chimpanzee) as active, although experimentation is necessary to support that this tRNA is actively transcribed. While nonsense suppression via readthrough by near-cognate tRNAs has been demonstrated several times in metazoa (Jungreis et al 2011;Yacoubi et al 2012;Loughran et al 2018;Roy et al 2015) and suppressor tRNAs have been found in other species (Beier and Grimm 2001;Valle, Morch, and Haenni 1987), evidence for an actively transcribed suppressor tRNA in a primate species is of great interest for future experimentation. This tRNA gene is a wellconserved ortholog of the human tRNA-Gln-CTG-6-1 gene, and exhibits several chimpanzee-specific nucleotide substitutions ( Supplementary Figure 4) that are not expected to significantly impair the function of its transcript.…”
Section: Figure 2: Classification Of Expression Based On Genomic Datamentioning
confidence: 99%
“…Several mammalian genes such as HBB, MPZ, VEGFA, OPRK1, OPRL1, AQP4, MAPK10, LDHB, MDH1, and VDR have been experimentally validated as PTR targets (Chittum et al, 1998;Yamaguchi et al, 2012;Eswarappa et al, 2014;Loughran et al, 2014Loughran et al, , 2018. The significance of this process in mammals is largely undetermined .…”
Section: Introductionmentioning
confidence: 99%
“…The significance of this process in mammals is largely undetermined . Several mammalian genes such as HBB, MPZ, VEGFA, OPRK1, OPRL1, AQP4, MAPK10, LDHB, MDH1, and VDR have been experimentally validated as PTR targets (Chittum et al, 1998;Yamaguchi et al, 2012;Eswarappa et al, 2014;Loughran et al, 2014Loughran et al, , 2018. Several more have been predicted to undergo translational readthrough whose regulation and physiological significance remain to be characterized (Jungreis et al, 2011;Dunn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Readthrough of the vitamin D receptor mRNA sequence UGACUAG results in an expression of a protein with 67 amino acid-long C-terminal extension (vitamin D receptor X). This longer proteoform is characterized by a reduced transcriptional response to calcitriol [47]. An interesting example of premature stop codon readthrough is the LAMA3 gene (R943X/R1159X).…”
Section: Discussionmentioning
confidence: 99%